Assessing the relationship between dyslexia, psychological distress, and academic self-efficacy among Nigerian university undergraduates - Bede C. Akpunne; Oladoyin Idowu; Daniel O. Kumuyi; Elizabeth N. Akpunne (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Academic self-efficacy refers to the student's beliefs and attitudes toward their capabilities to achieve academic success, as well as belief in their ability to fulfil academic tasks and the successful learning of the materials. The influence of dyslexia on academic self-efficacy and psychological distress among Nigerian students is underresearched in this study. This study investigated the relationship between dyslexia, psychological distress, and academic self-efficacy. MATERIALS AND METHOD: A total of 460 undergraduates purposively drawn from the University of Lagos, Nigeria, of over 10,000 undergraduate population, with a mean age of 26 ± 5 years, responded to the Academic Self-Efficacy Scale, the dyslexia adult checklist, the 12-item General Health Questionnaire, and Adult Reading History Questionnaire. Data were analyzed descriptively, and the regression analysis and T-tests were used for statistical analysis, with a significance threshold of P < 0.05. RESULTS: The results showed that dyslexia is a significant predictor of academic self-efficacy (β = 0.34, t = 7.31, P < 0.01). Dyslexia strongly predicted performance in examination [β = 0.32, F = 48.18, P = 0.00], comprehension [β = 0.32, F = 33.54, P = 0.00], school adjustment [β = 0.32, F = 35.86, P = 0.00], reading skill [β = 0.21, F = 18.65, P = 0.00], working memory [β = 0.26, F = 28.5, P = 0.00], and time management [β = 0.21, F = 19.8, P = 0.00] among the undergraduates. In addition, dyslexia significantly predicted psychological distress [t 41) = 1.40, P = 0.65]. Gender had no significant influence on academic self-efficacy and psychological distress among the participants [t 41) = 1.33, P = 0.19]. CONCLUSION: Dyslexia is a strong predictor of academic self-efficacy and psychological distress. Male and female Nigerian undergraduates have similar academic self-efficacy and psychological distress.